An Awareness of Pharmacovigilance Among Healthcare Professionals Due to an Underreporting of Adverse Drug Reactions Issue: A Systematic Review of the Current State, Obstacles, and Strategy - Putri, Risani A.; Ikawati, Zullies; Rahmawati, Fita; Yasin, Nanang Munif (Current Drug Safety, 2024)
Background: Healthcare professionals play an essential role in reporting adverse drug reactions as part of pharmacovigilance activities. However, adverse drug reactions reported by healthcare professionals remain low. Objective: The aim of this systematic review was to investigate healthcare professionals' knowledge, awareness, attitude, and practice on pharmacovigilance and adverse drug reaction reporting, explore the causes of the underreporting issue, and provide improvement strategies. Methods: This systematic review was conducted using four electronic databases for original papers, including PubMed, Scopus, Google Scholar, and Scholar ID. Recent publications from 1st January 2012 to 31st December 2022 were selected. The following terms were used in the search:
Keywords: HCP